Research Performance in Anesthesiology and Pain Medicine by Saudi Arabia - Rakan Khalid Al Fouzan, Ikram Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: A medical practice known as anesthesia, prevents patients from feeling pain before, during and after surgical procedure. The present study aims to present the bibliometric evaluation of the Saudi Arabian research in Anesthesiology and Pain Medicine (APM) during the last 40 years from 1983 to 2022. Method: The meta-data was retrieved on 31st August 2023 from the Scopus database for conducting bibliometric research. An advance search option was used, and selected the sub-category “Anesthesiology and Pain Medicine” from the major subject area of Medicine. We excluded the documents published after 31st December 2022. We downloaded the global summary of publications on APM and later selected the Saudi Arabia from the country filter and downloaded the bibliographic information of the documents. Microsoft Excel and VOSviewer software were used for data analysis. Results: A total of 207,683 documents were found on APM worldwide and the highest number of documents has been contributed by the United States (39%). About 41% of the documents were published in the last five years (2018-2022). Saudi Arabian authors produced 1,085 (0.52%) documents in 40 years from 1983 to 2022. More than half of the documents were published in the last five years and the ratio of open-accessed documents was found higher as compared to subscription-based documents. Saudi authors collaborated with authors from 109 countries but most of the research was performed with Egypt and the United States. Saudi Journal of Anaesthesia was the most frequent source of publication. The major funding sources and most occurred keywords were also analyzed. Conclusion: The current study has examined the research growth on APM produced by Saudi Arabia for 40 years. Overall, the share of Saudi Arabia in APM research at the global level was recorded at 0.52 percent, but the share was a bit increased and reached on 0.70 percent during the last five years of study. This increase has been strongly correlated with government investment in human resources and the development of healthcare and educational infrastructure. Keywords: Bibliometric, Anesthesia, Research productivity,